The Regulations of Order and Prohibition by the Fundamentalists in Quran - Al-Samra'i, Mohammad; Ahmad, Salih (Journal of Tikrit university for humanities - مجلة جامعة تكريت للعلوم الانسانية, 2019)
In this research, I have come up with a number of results. The most important of which are: The order has different versions as well as the prohibition has multiple versions, which came by the Koranic verses, and these formulas are different as required by the appropriate situation and verse. The commands of Allaah in the Qur'an and his prohibitions are restricted by the rules mentioned in details by the fundamentalists. In my research, I explained the necessity and the prohibition, do they require immediate action or not, and I mentioned the fundamental difference in this issue in detail. I have concluded through my research that it is different in terms of the obligation, the mandate and the permissibility.